THE IN VITRO ANTIMICROBIAL AND ANTIBIOFILM ACTIVITY OF HERBAL EXTRACTS - Sandasi, M.; Viljoen, A.; Leonard, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The in vitro antimicrobial and antibiofilm activity of thirty-two extracts (water and dichloromethane/methanol) from sixteen dietary spices and medicinal herbs were investigated against three pathogenic microorganisms (Listeria monocytogenes, Pseudomonas aeruginosa and Candida albicans). The antimicrobial activity was determined using the minimum inhibitory concentration (MIC) microtitre plate assay. The extracts that showed the highest antimicrobial activity against all the test organisms were turmeric, rosemary, thyme, echinacea, peppermint and tea tree with MIC values of ≤ 2 mg/ml. The growth and development of biofilms was assessed using the crystal violet (CV) assay and confocal scanning laser microscopy (CSLM) was used to visually assess the morphological changes and composition of the biofilm. The majority of the extracts tested prevented cell adhesion to the polyvinyl chloride (PVC) surface. The extracts that showed the greatest inhibition against all the test organisms were peppermint, rosemary and echinacea with inhibition values of ≥ 50%. In contrast, growth inhibition of an already established biofilm was more difficult to achieve. In most cases the extracts enhanced the growth of the biofilms. Peppermint was the only extract that showed antibiofilm activity against all the pathogens. The reduction of biofilm mass by use of plant extracts shows potential in anti-adhesion therapy thus reducing the incidence of diseases associated with biofilm formation.